"All Right, I Give Up. What is Digital Humanities?". (1st April 2021) - Wieringa, Jeri
Abstract : The digital turn impacts not only how scholars of religion present their research, but also how they conduct their research. Jeri Wieringa introduces readers to the digital humanities, the tools it employs, and the questions it raises for scholars of religion. While situating this subfield within the broad humanities, the essay highlights key examples demonstrative of how it manifests within religious studies.